The Construct of Subaltern Consciousness in Khaled Hosseini’s The Kite Runner - Bodke, Kailas N. (SMART MOVES JOURNAL IJELLH, 2019)
The Kite Runner is Afghanistan-American novelist, Khaled Hosseini’s best-selling debut novel. It’s an enduring story of betrayal and redemption that presents uprising agitation in modern Afghanistan. The Kite Runner brings to the fore many different issues throughout the novel; one such issue is the representation of Subalterns. According to Gayatri Spivak the Subalterns can’t speak for themselves; they are always spoken for by others. Here an attempt is made by the writer to represent the Subalterns i.e. the Hazaras and the women characters (both Hazaras and ethnic Pashtuns). The consciousness of Subalterns is constructed thorough the story of Amir, which brings forth the stark face of modern Afghanistan. The discrimination against the Hazaras (a marginalized class) is the most obvious form of social marginalization in The Kite Runner. They are treated badly by many of the dominant Pashtuns before the Russian takeover, and the Taliban gain control. The Hazaras are threatened to ethnic cleansing. Afghan women face a second-class stature in both their homeland and in America. The Taliban force all women to cover themselves in the traditional Burkha and impose strict laws that restrict their right to travel or appear in public places. This paper is an attempt to investigate the narrative through the insights provided by the characters through their mute sufferings and conformity to the culture they are part of